INDOGLISH IN SELECTED INDONESIAN SOCIAL MEDIA COMMENTS: A QUALITATIVE ANALYSIS - Karisma Erikson Tarigan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The rise of "Indoglish," a hybrid language that combines Indonesian and English in online communication, is one way that the growing use of social media has impacted bilingual communication habits among Indonesian users. The purpose of this study is to describe how Indoglish reflects social and digital communication patterns among Indonesian social media users, as well as to identify the many forms of code-mixing employed in Indoglish expressions and assess their communicative purposes. This study used a sociolinguistic approach in conjunction with a descriptive qualitative method. Twenty-five Indonesian social media comments using Indoglish expressions that were gathered using a documentation technique made up the data. Hoffman's communicative function theory, Muysken's theory of code-mixing, and sociolinguistic viewpoints on digital communication were used to analyze the data. Four types of code- mixing were identified by the results: intra-sentential, alternation, insertion, and tag switching. In the comments, intra-sentential code-mixing was the most common of these categories. Furthermore, the analysis demonstrated that Indoglish fulfilled a number of communicative purposes, such as identity- related, religious, persuasive, supportive, expressive, and solidarity. Additionally, the results show that Indoglish reflects modern digital communication techniques related to online identity formation, audience interaction, and emotional expression. According to the study's findings, Indoglish is a dynamic multilingual communication technique used in Indonesian social media interactions Keywords: Code-Mixing, Digital Communication, Indoglish, Social Media, Sociolinguistics. Abstrak: Meningkatnya penggunaan media sosial telah memengaruhi kebiasaan komunikasi bilingual di kalangan pengguna Indonesia, salah satunya melalui munculnya “Indoglish,” yaitu bahasa hibrida yang menggabungkan bahasa Indonesia dan bahasa Inggris dalam komunikasi daring. Penelitian ini bertujuan untuk mendeskripsikan bagaimana Indoglish merefleksikan pola komunikasi sosial dan digital di kalangan pengguna media sosial Indonesia, serta mengidentifikasi berbagai bentuk campur kode yang digunakan dalam ekspresi Indoglish dan menilai fungsi komunikatifnya. Penelitian ini menggunakan pendekatan sosiolinguistik dengan metode deskriptif kualitatif. Data penelitian berupa dua puluh lima komentar media sosial berbahasa Indoglish yang dikumpulkan melalui teknik dokumentasi. Data dianalisis menggunakan teori fungsi komunikatif Hoffman, teori campur kode Muysken, serta perspektif sosiolinguistik mengenai komunikasi digital. Hasil penelitian mengidentifikasi empat jenis campur kode, yaitu intra-sentensial, alternasi, penyisipan, dan tag switching. Di antara kategori tersebut, campur kode intra-sentensial merupakan jenis yang paling dominan ditemukan dalam komentar. Selain itu, analisis menunjukkan bahwa Indoglish memiliki berbagai tujuan komunikatif, seperti fungsi identitas, religius, persuasif, suportif, ekspresif, dan solidaritas. Hasil penelitian juga menunjukkan bahwa Indoglish mencerminkan teknik komunikasi digital modern yang berkaitan dengan pembentukan identitas daring, interaksi audiens, dan ekspresi emosional. Berdasarkan temuan penelitian, Indoglish dapat dipahami sebagai teknik komunikasi multilingual yang dinamis dalam interaksi media sosial di Indonesia.Kata Kunci: Campur Kode, Komunikasi Digital, Indoglish, Media Sosial, Sosiolinguistik.